PENINGKATAN PENGETAHUAN DAN KETERAMPILAN ORANG TUA GUNA MENCEGAH PERUNDUNGAN UNTUK MEWUJUDKAN DESA LAYAK ANAK BERBASIS KEARIFAN LOKAL DI DESA KERTAGENA DAJAH - Anna Aisa; Sri Rizqi Wahyuningrum; Diana Vidya Fakhriyani; Abbadi Ishomudin; Ishlakhatus Sa’idah; Misnawi (CV. Jendela Gagasan, 2025)
Bullying is a form of aggressive behavior, typically carried out intentionally and repeatedly by children or other individuals, with the aim of hurting others in order to gain personal satisfaction or happiness. This highlights the critical role of parents in helping children prevent such behavior. This community service project aims to enhance parents' knowledge and skills in preventing bullying, in order to foster a child-friendly and child-appropriate village environment. The methods employed include classical guidance sessions and communication skills training, using a Participatory Action Research (PAR) approach. The program emphasizes community support and involvement throughout all activities. The outcomes of this program show an increase in parents' understanding and abilities, as evidenced by their enthusiasm during discussions, Q&A sessions, and practical role-plays demonstrating healthy communication between parents and children. These improvements contribute to the prevention of bullying behavior among children and support the realization of a child-friendly village.